2020
DOI: 10.12659/msm.926086
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter-2 Inhibitor Immediately Decreases Serum Uric Acid Levels in Type 2 Diabetic Patients

Abstract: Background Sodium-glucose cotransporter-2 (SGLT2) inhibitors are new antihyperglycemic drugs for type 2 diabetes. SGLT2 inhibitors ameliorate cardiovascular morbidity and mortality as well as kidney disease progression by reducing body weight (BW), blood pressure (BP), visceral adiposity, albuminuria, and serum uric acid and blood glucose levels. However, it is not clear which effects are pronounced, and what mechanisms are associated with these effects. Material/Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Similar to our result, previous studies have shown that SGLT2i increase FEUA and decrease serum UA levels in patients with type 2 DM 14 17 . Ohashi et al reported that SGLT2i increased FEUA (before administration; 5.98 ± 2.59% vs. after administration; 7.71 ± 3.22%) and reduce serum UA levels (before administration; 6.13 ± 1.36 mg/dL vs. after administration; 5.20 ± 1.11 mg/dL) in patients with type 2 DM whose eGFR was 63.25 ± 24.66 mL/min/1.73 m 2 17 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to our result, previous studies have shown that SGLT2i increase FEUA and decrease serum UA levels in patients with type 2 DM 14 17 . Ohashi et al reported that SGLT2i increased FEUA (before administration; 5.98 ± 2.59% vs. after administration; 7.71 ± 3.22%) and reduce serum UA levels (before administration; 6.13 ± 1.36 mg/dL vs. after administration; 5.20 ± 1.11 mg/dL) in patients with type 2 DM whose eGFR was 63.25 ± 24.66 mL/min/1.73 m 2 17 .…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, allopurinol did not improve renal outcomes 12 , 13 . One of the pleiotropic effects of SGLT2i is reduction of serum UA in patients with type 2 diabetes mellitus (DM) whose estimated glomerular filtration rate (eGFR) was maintained at > 60 ml/min/1.73 m 2 14 17 ; however, the effect of lowering serum UA levels by SGLT2i in patients with CKD whose renal function reduced to ˂60 ml/min/1.73 m 2 is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…By increasing glucose concentration in the proximal tubule, where it competes with uric acid for the transporter GLUT9b, SGLT2is reduce reabsorption and promote uric acid urine excretion [ 26 , 41 , 42 ], probably contributing to reduce renal, cardiovascular and mortality risk [ 43 , 44 , 45 ]…”
Section: Mechanisms Of Renal Protection With Sglt2mentioning
confidence: 99%
“…By increasing glucose concentration in the proximal tubule, where it competes with uric acid for the transporter GLUT9b, SGLT2is reduce reabsorption and promote uric acid urine excretion [26,41,42], probably contributing to reduce renal, cardiovascular and mortality risk [43][44][45] In addition, it was suggested that SGLT2is may indirectly inhibit URAT1 through several mechanisms [46,47], including reduction in insulin secretion due to improvement in glucose metabolism [48]. However, serum UA changes induced by SGLT2is may be masked in CKD patients as glycosuria becomes smaller along with GFR reduction.…”
Section: Uric Acidmentioning
confidence: 99%
“…Sodium-glucose cotransporter-2 (SGLT2) inhibitors induce glucosuria. Ohashi et al [14] reported that their administration enhanced the fractional excretion of glucose from 1.46 to 27.81% in 24 type-2 diabetic patients. Accordingly, the glucosuria observed in this study is comparable to that induced by the administration of SGLT2 inhibitors.…”
Section: Discussion/conclusionmentioning
confidence: 99%